A galactose-rich heteropolysaccharide extracted from "jaboticaba" (Plinia cauliflora) peels. (1st December 2020) - Miranda, Bruna M.; Di-Medeiros, Maria C.B.; Batista, Karla A.; Carbonero, Elaine R.; Fernandes, Kátia F.; Silva, Flávio A.
Highlights: "Jaboticaba" peels represent a promising source of a thickener polysaccharide. GH was isolated and characterized for the first time from "jaboticaba" peels. "Jaboticaba"peel's polysaccharide is an arabinogalactan. Abstract: The objective of this work was to extract, identify and characterize a galactose-rich heteropolysaccharide (GH) from "jaboticaba" peel. The best conditions to extract the GH according to a 2 3 full-factorial experimental design were 90 °C/30 min/pH 1.0, resulting in a 32.32 % yield using lyophilized sample. The chemical structure analyzed by GC/MS and NMR spectra (HSQC/HSQC-TOCSY) showed that the main chain of GH consists of a (1→4) galactoside branched at carbon 3, containing galactose (67.21 %), glucose (15.78 %), arabinose (9.78 %), rhamnose (2.26 %) and traces of esterified and non-esterified uronic acids. Rheological studies revealed that GH suspensions behave as a Newtonian fluid, with calculated molecular mass of 1.48 × 10 5 Da. The absolute viscosity of 1 % (w/v) aqueous suspension of GH decreased from 25 mPa s to 10 mPa s in NaCl and 7 mPa s in CaCl2, indicating the polyelectrolyte character of GH.